Development of an LMS prototype to improve the learning of higher basic education students applying the flipped classroom methodology - Guilcatoma-Peñaherrera, María (2023)
Currently, problems related to academic performance are observed in higher basic education students, not only in subjects that have traditionally been considered of a certain level of complexity, such as in the area of exact sciences, mathematics and physics or chemistry, but also in socio-humanistic areas such as art education. In response to this situation, an attempt has been made to address the problem with a view to improving student performance in order to avoid school failure and dropout. In this sense, innovative methodologies have emerged to solve this situation. One of them is the Flipped Classroom, which is characterized by using information and communication technologies to improve student learning with the use of digital educational resources in the classroom or outside of it, thus favoring not only the understanding, application of knowledge and improvement of school performance, but also the stimulation of students' interest by considering themselves as protagonists and main actors in their learning process. This study proposes the development of a Learning Management System (LMS) to improve student learning. This LMS prototype uses the Flipped Classroom Methodology applied in one syllable during a period of one month in the subject of cultural and artistic education. This subject is distributed as follows: 1.- Initial Assessment; 2.- Heritage; 3.- Types of Heritage; 4.- Cultural Heritage; 5.- Natural Heritage; 6.- Final evaluation. The study had a sample of 12 students, evaluated before and after the proposal on the topics included in the prototype. The findings of this study showed a prior knowledge of the proposal of 21.7% and a knowledge of 90% after the application of the proposal, observing that most of the students reached an optimal level of knowledge.